Cosmology and gravitation - Maia, Marcos Duarte (2004)
This is a brief summary with comments on selected contributions to the Cosmology and Gravitation section at the 24th Brazilian Meeting on Particle and Fields (ENFPC XXIV), held at Caxambu, from September 30 to October 4, 2003.